Systematic Literature Review: Pengaruh Warna Orange terhadap Persepsi Kedalaman (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
Depth perception is a crucial visual ability for humans to judge distance and understand three-dimensional space. However, the brain's distance estimation is not always accurate and is often influenced by external factors such as color. This study aims to examine in depth how orange color influences the acuity of human depth perception. The method applied is a Systematic Literature Review (TLS) by examining 8 research papers from repository data from Google Scholar and ScienceDirect databases ranging from 2007 to 2025. The results show that orange, as part of the warm color spectrum with a long wavelength, significantly creates an advancing color effect that makes objects perceived as closer than cool colors. The main findings reveal that orange provides superior visual acuity in low-light conditions and has a wide stereoscopic disparity range to help the brain map space. In conclusion, the color orange functions as an effective additional visual cue in strengthening spatial perception. The implications of this research are highly relevant for the development of Augmented Reality (AR) technology and visual safety design, where the use of orange can minimize distance estimation errors by users